2022
DOI: 10.3390/w14081299
|View full text |Cite
|
Sign up to set email alerts
|

Green Energy and Water Resource Management: A Case Study of Fishery and Solar Power Symbiosis in Taiwan

Abstract: Renewable energy development is a key pathway for mitigating climate change. The Taiwan government has been actively developing low carbon green energy with solar photovoltaic technology and wind power as their primary development projects. Cigu Taiwan provides an ideal research site to examine tradeoffs between ecological conservation, marine fisheries, and green power development, and the factors affect commitments to ecological conservation in the face of these tradeoffs. This research investigates the fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Recent studies [24,25] have shown that farmers vary widely in terms of preferred compensation rates, compensation expectations and policy preferences due to cognitive heterogeneity. In addition, several studies suggest that economic, social and psychological features are related to satisfaction with the policy [26,27]. A study by Li et al (2022) on grassland ecological compensation programs found significant differences in herders' policy satisfaction influenced by factors such as household income, payment cognition, and the size of household-owned grasslands [13].…”
Section: Rural Households' Attitudes and Influencing Factorsmentioning
confidence: 99%
“…Recent studies [24,25] have shown that farmers vary widely in terms of preferred compensation rates, compensation expectations and policy preferences due to cognitive heterogeneity. In addition, several studies suggest that economic, social and psychological features are related to satisfaction with the policy [26,27]. A study by Li et al (2022) on grassland ecological compensation programs found significant differences in herders' policy satisfaction influenced by factors such as household income, payment cognition, and the size of household-owned grasslands [13].…”
Section: Rural Households' Attitudes and Influencing Factorsmentioning
confidence: 99%
“…Solar power generation is a zero-carbon, noise-free mode of producing electricity that can effectively reduce greenhouse gas emissions [30]. However, substantial amounts of land are required to achieve a certain level of power generation [31,32]. In Taiwan, where the land is narrow and densely populated, suitable land for the development of solar power is limited [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In exploring consumers’ WTP for green products, the choice experiment method (CE), with its ability to evaluate multiple attributes and levels, can combine different alternatives for important characteristics related to nonmarket goods or services, and enables respondents to state their preferences for hypothetical alternative scenarios. This method has been widely used in the fields of consumer behavior [ 42 , 43 ], sharing economy [ 44 , 45 ], green energy [ 46 , 47 ], tourism, and leisure [ 48 , 49 ]. In recent years, it has been gradually applied in the food industry [ 6 , 50 , 51 , 52 ].…”
Section: Literature Reviewmentioning
confidence: 99%